Understanding and acting on the developmental origins of health and disease in Africa would improve health across generations. Issue 1 (1st January 2017) - Norris, Shane A.; Daar, Abdallah; Balasubramanian, Dorairajan; Byass, Peter; Kimani-Murage, Elizabeth; Macnab, Andrew; Pauw, Christoff; Singhal, Atul; Yajnik, Chittaranjan; Akazili, James; Levitt, Naomi; Maatoug, Jihene; et al.
ABSTRACT: Data from many high- and low- or middle-income countries have linked exposures during key developmental periods (in particular pregnancy and infancy) to later health and disease. Africa faces substantial challenges with persisting infectious disease and now burgeoning non-communicable disease.This paper opens the debate to the value of strengthening the developmental origins of health and disease (DOHaD) research focus in Africa to tackle critical public health challenges across the life-course. We argue that the application of DOHaD science in Africa to advance life-course prevention programmes can aid the achievement of the Sustainable Development Goals, and assist in improving health across generations. To increase DOHaD research and its application in Africa, we need to mobilise multisectoral partners, utilise existing data and expertise on the continent, and foster a new generation of young African scientists engrossed in DOHaD.